Obstacles to Women’s Higher Education in Nepal: A Critical Review of Policies and Practices - Bhandari, Ganga Laxmi (Education and Development, 2019)
This article critically reviews the theoretical and practical issues posing barrier to women for pursuing higher education and reaching professionally leading position in the Nepalese education sector. This article is based on the secondary resources such as cases and materials available in the public domain, and writer’s own experiences. The study concludes that Nepali women are facing numerous obstacles in all sectors, from household to public institution as well as in the education sector. However, the nature and intensity of obstacles differ among certain ethnic groups.